A novel thermostable cellulase-producing Bacillus licheniformis A5 acts synergistically with Bacillus subtilis B2 to improve degradation of Chinese distillers' grains. (April 2021) - Yang, Gang; Yang, Diqin; Wang, Xiaodan; Cao, Wentao
Graphical abstract: Highlights: The first report on CDGs degradation by bacterial co-cultures. Cellulase produced by B. licheniformis A5 is active and stable at 80 °C. Synergistic effect of B. licheniformis A5 and B. subtilis B2 degrades on CDGs. 2% ethanol increases degradation rate of CDGs. Abstract: Lack of effective degradation approaches of Chinese distillers' grains (CDGs) produced by Chinese liquor industry results in environmental pollution and economic waste. Cellulase activity was characterized at different temperatures to find thermostable cellulase-producing bacteria, and microbial co-culture method was used to improve the degradation of CDGs. Incubation of endoglucanase produced by Bacillus licheniformis A5 at 80 °C for 120 min showed 82% residual enzyme activity. Notably, enzyme activity increased by 30%-70% after co-culturing Bacillus licheniformis A5 and Bacillus subtilis B2. The two strains increased degradation rate of CDGs by 70% compared with optimized results of Bacillus subtilis B2 culture alone, and increased the reducing sugar content to 16.6 mg/mL. In addition, 2% ethanol increased degradation rate of CDGs by 15% in co-culture. The findings of this study imply that Bacillus licheniformis A5 acts synergistically with Bacillus subtilis B2 to improve degradation of CDGs.